2010
DOI: 10.1007/s12223-010-0109-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Plesiomonas spp.: Serological and MALDI-TOF MS methods

Abstract: Biochemical and serological profiles of isolates of Plesiomonas shigelloides were assayed using standard procedures in isolates from various clinical samples. Seventy-four isolates, including P. shigelloides type strain, were further characterized by MALDI-TOF MS using 3-methoxy-4-hydroxycinnamic acid as matrix. Multiple ions in the 3- to 12-kDa mass range were found in the spectra of each strain, from which the "species-identifying" unique biomarker ions were identified. After creating the species-specific pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Seventyfour isolates were identified as Plesiomonas shigelloides by biochemical methods and serologically typed prior to analysis by MALDI-TOF MS, with Aeromonas and Shigella isolates being used as outgroups for comparison. A database was constructed de novo, and the authors determined that MALDI-TOF MS was suitable for the identification of Plesiomonas shigelloides, but there was no correlation between the spectral profiles generated and serogrouping results (179).…”
Section: The Enterobacteriaceaementioning
confidence: 99%
“…Seventyfour isolates were identified as Plesiomonas shigelloides by biochemical methods and serologically typed prior to analysis by MALDI-TOF MS, with Aeromonas and Shigella isolates being used as outgroups for comparison. A database was constructed de novo, and the authors determined that MALDI-TOF MS was suitable for the identification of Plesiomonas shigelloides, but there was no correlation between the spectral profiles generated and serogrouping results (179).…”
Section: The Enterobacteriaceaementioning
confidence: 99%
“…Likewise, among the molecular tools focused on the genotyping of isolates for phylogenetic and epidemiological studies are multilocus sequence typing (MLST), random amplified polymorphic DNA (RAPD)-PCR, enterobacterial repetitive intergenic consensus (Eric)-PCR, repetitive extragenic palindromic (REP)-PCR, and pulsed field gel electrophoresis (PFGE) [ 80 , 81 ]. Meanwhile, there are techniques for the identification and phenotypic characterization of bacterial isolates based on the analysis of proteins (mainly ribosomal) through the creation of a specific mass spectrum of genus and species (fingerprint) based on the sensitivity, accuracy, speed, and reproducibility of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) [ 36 , 82 , 83 ].…”
Section: Control and Prevention Of Diseases In Humans Due To Plesiomonas Shigelloidesmentioning
confidence: 99%
“…Also, matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry (MALDITOF MS) instrumental methods have been used for proteomics, structural and molecular characterization of P. shigelloides’ lipopolysaccharide (LPS), and serotype (strain) delineation based on the O-PS side chain of LPS-variable chemical units as well as genetic variability in the wb cluster genes [ 11 ]. However, it has been shown that MALDITOF MS characterization of P. shigelloides lacks similarity between the same sero-strains [ 12 ].…”
Section: Introductionmentioning
confidence: 99%